IMPROVING BITEWING RADIOGRAPHY: EVALUATING THE EFFECT OF A DENTAL X-RAY POSITIONER ON IMAGE QUALITY IN DENTAL EXAMINATIONS - Marichatul Jannah; Ardi Soesilo Wibowo; Agustina Dwi Prastanti; Wingghayarie Patra Gandhi (Poltekkes Kemenkes Semarang, 2023)
Bitewing radiography is a valuable tool in detecting and monitoring dental decay and other oral health problems and is typically performed as part of a routine dental examination. It has certain limitations that should be considered. Some of these limitations may cause discomfort or pain to the patient if not positioned correctly. Some patients may find biting down on the film holder difficult or have a strong gag reflex, making the procedure uncomfortable or even impossible. Bitewing radiography can be costly, especially if it needs to be performed regularly, which may limit access to this diagnostic tool for some patients. This study aimed to evaluate the effect of a dental X-ray positioner with a silicone layer on the quality of radiographic images in posterior bitewing dental examinations. Using this positioner was expected to improve the precision of radiographic interpretation and subsequent patient treatment. The study used a multivariate general linear model to analyze the data obtained from radiographic images using the X-ray positioner with the silicone layer and the conventional X-ray positioner. The results showed no significant difference in image quality between the two positioners, indicating that adding the silicone layer did not significantly improve image quality. However, using any X-ray positioner is still beneficial in ensuring accurate radiographic interpretation and subsequent patient treatment.